Management of Pancreatic Neuroendocrine Tumors - Pisegna, Joseph R.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2015)
This book provides the reader with a multidisciplinary approach that is state of the art and reflects input from the European Neuroendocrine Tumor Society and the North American Neuroendocrine Tumor Society. In particular, the text focuses on the pathophysiology of neuroendocrine tumors and includes a comprehensive review of the most recent developments in understanding the complex hormone and receptor signaling that is important for the future development of potent pharmacological treatments. The volume reviews the pathological grading and staging systems providing useful clinical information for the treating clinician as well as a useful reference for pathologists. The clinical management of neuroendocrine tumors is reviewed enabling the treating physician to understand the diagnostic approaches to differentiating the various types of neuroendocrine tumors. In addition, the treatments are reviewed in great detail and include novel radiological, surgical, and chemotherapeutic approaches. The reader will utilize this book as both a comprehensive and quick reference guide through the use of diagnostic and treatment algorithms. Written by international experts in their particular field of study, Management of Pancreatic Neuroendocrine Tumors will be of great value to medical oncologists, endocrinologists, gastroenterologists, pathologists, surgeons, and diagnostic and interventional radiologists.
Pathology of Pancreatic Neuroendocrine Tumors -- Inherited and Somatic Genetics of Pancreatic Neuroendocrine Tumors -- Laboratory Assessment of NETS -- Zollinger-Ellison Syndrome: Diagnosis and Management -- Clinical Manifestations of Multiple Endocrine Neoplasia, Type 1 -- Gastric Carcinoids: Classification and Diagnosis -- Endoscopic Approaches for Diagnosis of Pancreatic Neuroendocrine Tumors -- Endoscopic Approaches to Treatment of Pancreatic Neuroendocrine Neoplasms -- Surgical Approaches to Neuroendocrine Tumors -- Radiotherapy and Radiopharmaceuticals for the Treatment of Pancreatic Neuroendocrine Tumors -- Nuclear Medicine Approaches to Treatment of Neuroendocrine Tumors -- Novel Targets for Future Medical Treatments.
Keywords: Gastroenterology .; Endocrinology .; Oncology .; Radiology; Gastroenterology; Endocrinology; Oncology; Diagnostic Radiology